Detection of hepatitis C virus resistant mutants in the era of direct acting antivirals - Rossi, Livia Maria Gonçalves [UNESP]; Rahal, Paula [UNESP] (Science Publications, 2014)
Hepatitis C Virus (HCV) infects millions of people and represents an important public health problem in different regions of the world. Drug resistance is a major challenge for HCV-infection related control. Importantly, the arrival of a plethora of novel, more powerful drugs has revolutionized the field of HCV treatment. Here, we discuss the relevance of identification of HCV resistant mutants from a clinical standpoint. The advantage and limitations of molecular testing in clinical setting is presented.
Keywords: Direct acting-antiviral; Hepatitis C virus; Resistant mutants; Therapy